Kosovo 1989: The (Ab)use of the Kosovo Myth in Media and Popular Culture - Vučetić Radina (Comparative Southeast European Studies)
The author explores the creation of public opinion in Serbia in the late 1980s and the (ab)use of the 600th anniversary of the Battle of Kosovo on 28 June 1989. As a result of Serbian president Slobodan Milošević’s carefully planned propaganda, a negative image of Albanians as well as a positive perception of Serbian nationalism were enforced. The media and popular culture played a particularly important role in reviving the Kosovo Myth, together with the leading Serbian (academic) institutions and influential intellectuals. Thirty-some years after 1989, the Kosovo Myth is presented in the media in a largely unchanged manner, while for Serbia the Kosovo problem remains unsolved.